Performing Site-Specific Theatre
XV, 253 p.
Keywords: This book investigates the expanding parameters for site-specific performance to account for the form's increasing popularity in the twenty-first century. Leading practitioners and theorists interrogate issues of performance and site to broaden our understanding of the role that place plays in performance and the ways that performance influences it.